Adsorptive removal of iodate oxyanions from water using a Zr-based metal–organic framework. Issue 21 (8th February 2023) - Copeman, Christopher; Bicalho, Hudson A.; Terban, Maxwell W.; Troya, Diego; Etter, Martin; Frattini, Paul L.; Wells, Daniel M.; Howarth, Ashlee J.
Abstract : A zirconium cluster-based metal–organic framework, MOF-808, is evaluated for the adsorption of iodate oxyanions from water. Abstract : A Zr6 -based metal–organic framework (MOF), MOF-808, is investigated for the adsorptive removal of IO3 − from aqueous solutions, due to its high surface area and abundance of open metal sites. The uptake kinetics, adsorption capacity and binding mode are studied, showing a maximum uptake capacity of 233 mg g −1, the highest reported by any material.